Lithium-mediated protection against ethanol neurotoxicity - Luo, Jia (Frontiers in Neuroscience, 2010)
Lithium has long been used as a mood stabilizer in the treatment of manic-depressive (bipolar) disorder. Recent studies suggest that lithium has neuroprotective properties and may be useful in the treatment of acute brain injuries such as ischemia and chronic neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease and amyotrophic lateral sclerosis. One of the most important neuroprotective properties of lithium is its anti-apoptotic action. Ethanol is a neuroteratogen and fetal alcohol spectrum disorders (FASD) are caused by maternal ethanol exposure during pregnancy. FASD is the leading cause of mental retardation. Ethanol exposure causes neuroapoptosis in the developing brain. Ethanol-induced loss of neurons in the central nervous system underlies many of the behavioral deficits observed in FASD. Excessive alcohol consumption is also associated with Wernicke–Korsakoff syndrome and neurodegeneration in the adult brain. Recent in vivo and in vitro studies indicate that lithium is able to ameliorate ethanol-induced neuroapoptosis. Lithium is an inhibitor of glycogen synthase kinase 3 (GSK3) which has recently been identified as a mediator of ethanol neurotoxicity. Lithium’s neuroprotection may be mediated by its inhibition of GSK3. In addition, lithium also affects many other signaling proteins and pathways that regulate neuronal survival and differentiation. This review discusses the recent evidence of lithium-mediated protection against ethanol neurotoxicity and potential underlying mechanisms.